The study on the molecular characteristics and variation patterns of the recombinant Muscovy duck parvovirus strain GD-23 - Mingtian Mao; Jiake Li; Caiqi Wang; Mian Wu; ChengGuang Lu; Yudong Zhu; HuiHui Li; Bing Li; Meixi Lu; Yi Tang (Virulence, 2025)
As the virus continues to spread, the frequency of contact between different parvovirus strains has increased. In recent years, recombinant Muscovy duck parvovirus (rMDPV) has been widely prevalent in China. In 2023, a strain of rMDPV, designated GD-23, was isolated from Guangdong. After isolation and culture, the entire genome of GD-23 was sequenced. A phylogenetic tree was constructed based on the genomic characteristics of GD-23, and recombination events were analysed. The analysis revealed that the virus underwent two recombination events between different parent strains in the P9 promoter region and part of the VP3 region, with highly consistent start and end breakpoints among rMDPV strains. Using AlphaFold3, the VP3 protein conformation of waterfowl parvoviruses (WPVs) was simulated, and potential receptor interaction regions were predicted based on the structural similarities of capsid proteins among viruses of the same genus. Notably, the rMDPV-GD-23 strain exhibited two identical amino acid mutations at distinct sites, which reduced the overall phosphorylation of the viral capsid. Artificial infection experiments in waterfowl demonstrated that the rMDPV-GD-23 strain was pathogenic to multiple waterfowl hosts. This study provides the first evidence that rMDPV possesses cross-host infection capability, a finding that will aid in identifying key amino acid sites on the capsid surface of WPVs.